2015
DOI: 10.1002/lary.25673
|View full text |Cite
|
Sign up to set email alerts
|

The role of Smad3 in the fibrotic phenotype in human vocal fold fibroblasts

Abstract: Objective To investigate the role of Smad3 as a regulator of transforming growth factor (TGF)-β1-mediated cell activities associated with fibrosis in normal human vocal fold fibroblasts. We also sought to confirm the temporal stability of Smad3 knockdown via siRNA. Vocal fold fibroblasts were employed to determine the effects of Smad3 knockdown on TGF-β1-mediated migration and contraction as well as regulation of connective tissue growth factor (CTGF). We hypothesized that Smad3 is an ideal candidate for thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 23 publications
6
58
0
Order By: Relevance
“…Lee et al recently demonstrated that suppression of Smad3 using a topical siRNA gel conferred resistance to radiation‐induced cutaneous fibrosis in a murine model . Our laboratory also has recently demonstrated that SMAD3 siRNA reduced the fibrotic phenotype in vocal fold fibroblasts in vitro . Most recently, our laboratory described successful knockdown of SMAD3 via local siRNA injection in a leporine model of vocal fold injury.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lee et al recently demonstrated that suppression of Smad3 using a topical siRNA gel conferred resistance to radiation‐induced cutaneous fibrosis in a murine model . Our laboratory also has recently demonstrated that SMAD3 siRNA reduced the fibrotic phenotype in vocal fold fibroblasts in vitro . Most recently, our laboratory described successful knockdown of SMAD3 via local siRNA injection in a leporine model of vocal fold injury.…”
Section: Discussionsupporting
confidence: 91%
“…Our laboratory and others have identified SMAD3 as a principle mediator of fibrotic VF wound healing due to its role in TGF‐β1 signaling, which in turn regulates numerous fibroblast activities including migration, proliferation, and production of extracellular matrix proteins . SMAD7 is a homolog of SMAD3 and serves as an antifibrotic regulator opposing the actions of SMAD3 through competitive inhibition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports suggested that GR inhibited TGF‐β signaling by directly targeting the transcriptional activation function of SMAD3, which is consistent with our data. Our laboratory and others identified SMAD3 as a principle mediator of fibrotic VF wound healing due to its role in TGF‐β1 signaling, which in turn regulates numerous fibroblast activities including migration, proliferation, and production of extracellular matrix . Clearly, these data suggest that DM has antifibrotic effects.…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, SMAD7 is a competitive inhibitor of SMAD activation, and therefore is thought to be antifibrotic. Activated Smads have been implicated in a variety of fibrotic processes, suggesting that Smad activation plays a central role in fibrosis . Ideally, therapies for vocal fold fibrosis should likely alter the fibroblast phenotype, and emerging data suggest that GCs attenuate TGF‐β/SMAD signaling in human fetal lung fibroblasts .…”
Section: Introductionmentioning
confidence: 99%